Analisis Materi Nahwu dalam Kitab at-Tuhfatu as-Saniyyah bi Syarhil Muqaddimah al-Jurumiyyah Karya Syaikh Muhammad Muhyiddin Abdul Hamid al-Mishri - Darwin Zainuddin; Fauzan Arif (EduInovasi: Journal of Basic Educational Studies, 2023)
This study aims to analyze nahwu material related to methods, systematics, addition and sampling in the book at-Tuhfatu as-Saniyyah bi Syarhi al-Muqaddimah al-Jurumiyyah. This research uses a descriptive qualitative method with a literature study approach. The results obtained from this study are that the book at-Tuhfatu as-Saniyyah uses the deductive method or thoriqoh qiyasiyyah. The systematics of the book at-Tuhfatu as-Saniyyah is the same as the book of Matan al-Jurumiyyah, namely 23 chapters but is equipped with more guidance or explanations and also additional examples. In the discussion of Jawazim al-Fi'li al-Mudhari' in the book at-Tuhfatu as-Saniyyah examples are taken from the Qur'an, Hadith, Mufidah Numbers and also Arabic Sya'ir-sya'ir. At the end of each chapter, questions and exercises are presented to evaluate understanding regarding the material presented previously. The book at-Tuhfatu as-Saniyyah is very suitable for Mubtadi and Muthawwasith who study Nahwu Science.